PENGARUH KEPUASAN KERJA TERHADAP KINERJA KARYAWAN MELALUI ORGANIZATIONAL CITIZENSHIP BEHAVIOR SEBAGAI VARIABEL INTERVENING (STUDI PADA STAFF PT KEPUH KENCANA ARUM MOJOKERTO - ARIANTO, DENY (Jurnal Ilmu Manajemen (JIM), 2017)
PT. Kepuh Kencana Arum was founded in 1991 in Mojokerto, East Java. At first the company is engaged in manufacturing roofing metal wave length without connection with trademark Kencana. Along with its development, the company adds to the product range in the form of a metal tile, lightly steel truss, and order planfond based raw material steel aluminium layer. This research aims to analyze the influence of job satisfaction on performance of employees through organizational citizenship behaviour as an intervening variable study on the staffs of PT Kepuh Kencana Arum Mojokerto. This research is quantitative approach. With a population of 35 staff were used and the sample used is saturated sample i.e. the whole staffs of PT Kepuh Kencana Arum Mojokerto totalling 35 staff. Data analysis technique used is a Structural Equation Model of Partial Least Square with the help of SmartPLS software 1.0. The results showed that job satisfaction has no effect on performance of employees with an average value of 0.193. While job satisfaction against direct influence and OCB there is significant with the average value of 0.620. There is also a direct and significant influence among variables OCB on performance of employees with an average value of 0.710. OCB was able to mediate the influence of job satisfaction on performance of employees. Keywords: Job Satisfaction, Organizational Citizenship Behavior (OCB), The Performance Of Employees